DAMPAK MIGRASI TERHADAP KESEJAHTERAAN MASYARAKAT DESA BUNIHARA KECAMATAN ANYER - Ardiyanti Safitri; Nia Sundari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Migration is a social phenomenon that occurs to individuals or groups who move from one place to another, usually to get better opportunities. Bunihara Village, Anyar District, Serang Regency is one of the villages where some people migrate for a better life because the job market in the village is very limited, so it is a motivating factor for its residents to migrate. But there are also other residents who migrate to Bunihara Village, Anyar District, Serang Regency with the aim of improving the quality of life for their families. This study aims to analyze the impact of migration on the welfare of the Bunihara Village community, Anyar District, Serang Regency. The research method used is a qualitative approach by conducting in-depth interviews with a number of migrants and local communities who are the target of the collected data being analyzed using the content analysis method by identifying patterns and findings related to the impact of migration on the welfare of the Bunihara Village community, Anyar District, Serang Regency. The results of the study indicate that migration can have a complex influence on the welfare of the Bunihara Village community, Anyar District, Serang Regency. On the one hand, migrants have helped to increase family income, improve access to education, and improve the quality of life. Many families who previously lived in limitations now have better changes. But on the other hand, there are also those who feel the decline in the number of workers in the village causing reduced local activities and changes in social structures. The loss of a young workforce has the potential to cause stagnation in village development. The conclusion of this study is that the impact of migration on the welfare of the community in Bunihara Village, Anyer District, Serang Regency cannot be viewed in one dimension. A more comprehensive approach is needed in managing migration and minimizing its negative impacts. It is important to involve all stakeholders in formulating sustainable policies such as local communities or migrants themselves.